Evaluation of eyes enucleated for scleritis. Issue 3 (March 1976) - Fraunfelder, F. T.; Watson, P. G.
Abstract : A series of 30 enucleated eyes, all of which had a primary histological diagnosis of scleritis, was analysed. The average age of patients at enucleation was 68 years; many of these patients had had the disease for more than 30 years. In 40 per cent the diagnosis of scleritis was unsuspected and was often masked by multiple complications. Scleritis with uveitis and glaucoma was the most common combination to come to enucleation. In 82 per cent, pain was the reason for enucleation, which suggests that some patients were on inadequate levels of steroid treatment or were unable to tolerate them. In the series, 37 per cent of the eyes perforated. Perforation occurred in those patients who were having steriods but not in those who were not, but the data are inconclusive as to which method of steroid administration was most likely to cause ocular perforation.